1995
DOI: 10.1029/95ja01675
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐mode shocks in the magnetotail

Abstract: We have identified slow-mode shocks between the plasma sheet and lobe in the midtail to distant-tail regions by using three-dimensional magnetic field data and three-dimensional plasma data including density, velocity, temperature, and heat flux of both ions and electrons observed by the GEOTAIL satellite. Analyzing the data obtained between September 14, 1993, and February 16, 1994, we have found 303 plasma sheet-lobe boundary crossings at distances between XGSE "'• -30RE and XGS E -,• -210RE. Thirty-two out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 30 publications
2
93
0
Order By: Relevance
“…The cold ions are heated and accelerated perpendicularly through slow-mode shocks (Omidi, 1995;Saito et al, 1995). The electron distribution functions in the downstream plasma sheet have a flat-top distribution along the magnetic field line (Feldman et al, 1985;Schwartz et al, 1987;Saito et al, 1995). The existence of backstreaming field-aligned ions in the upstream region from the slow-mode shock is well known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cold ions are heated and accelerated perpendicularly through slow-mode shocks (Omidi, 1995;Saito et al, 1995). The electron distribution functions in the downstream plasma sheet have a flat-top distribution along the magnetic field line (Feldman et al, 1985;Schwartz et al, 1987;Saito et al, 1995). The existence of backstreaming field-aligned ions in the upstream region from the slow-mode shock is well known.…”
Section: Discussionmentioning
confidence: 99%
“…From examination of a time sequence of the counterstreaming beams, we conclude that at least one of the two beams originated from cold ions in the lobe. The cold ions are heated and accelerated perpendicularly through slow-mode shocks (Omidi, 1995;Saito et al, 1995). The electron distribution functions in the downstream plasma sheet have a flat-top distribution along the magnetic field line (Feldman et al, 1985;Schwartz et al, 1987;Saito et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow shocks were observed in the distant tail (X<−100 R E ) on the lobe-plasma sheet boundary (e.g. Saito et al, 1995) and on the plasmoid boundaries at X∼−100 R E (Mukai et al, 1996). Recently, Eriksson et al (2004) reported observations of reconnection related shocks in the near-Earth tail.…”
mentioning
confidence: 97%
“…A small number of slow shocks have been observed in interplanetary space (Chao and Olbert, 1970;Burlaga and Chao, 1971;Richter et al, 1985;Whang et al, 1996) and in the magnetotail (Feldman et al, , 1985(Feldman et al, , 1987Smith et al, 1984;Seon et al, 1995;Saito et al, 1995Saito et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%